Analysis and Improvement of Production Process Activities of Arikyd 36xx HV Products at PT. Highpolymer Aristek with Manufacturing Cycle Effectiveness and Fishbone Diagram Technique - Natasya, Natasya (Ann Publisher, 2023)
PT. Aristek Highpolymer is a company engaged in the chemical industry by producing synthetic resins and polyurethanes. In carrying out its business processes, PT. Aristek Highpolymer produces 6 types of products, one of which is arikyd 36xx hv products. In carrying out the production process arikyd 36xx hv there is a delay due to high cycle time that affects effectiveness. With these problems, it is necessary to conduct an analysis of production process activities in order to find the root cause of delays and solutions that are expected to minimize or reduce delays that occur. In this study, the manufacturing cycle effectiveness (MCE) method will be used to be able to determine and improve production effectiveness and identify non-value-adding activities using Fishbone Diagram. From the results of research using the Manufacturing Cycle Effectiveness (MCE) method, the effectiveness of the production process was obtained by 74%, this shows that in carrying out the production process there are still activities not adding value by 26%. Then the root cause of the problem was identified using the fishbone diagram method and it was known that there were 4 main factors that became the problem of non-value added in the production process, namely: Lack of training in production activities, less ergonomic machines and lack of maintenance, Lack of tools in production process activities and inefficient production process layout.